2021
DOI: 10.1002/eahr.500095
|View full text |Cite
|
Sign up to set email alerts
|

Developing Biopsychosocial Research on Maternal Mental Health in Malawi: Community Perspectives and Concerns

Abstract: Interest in maternal mental health research is growing around the world. Maternal mental health research studies in Malawi have, for instance, sought to determine and establish the incidence and prevalence of depression and anxiety in pregnant people and the factors that contribute to experiences of these states. This article reports stakeholder perspectives on potential community concerns with biopsychosocial mental health research (which might include collecting blood samples) in Malawi. These perspectives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Through discussions with various stakeholders about this project specifically and MMH more generally, our study provides new insights into the acceptability and ethicality of MMH research in Malawi (and, indeed, population health research more broadly). Some of our findings reinforce and resonate with earlier studies on community perspectives around collecting biological samples in research, concerns around researchers' perceived intentions, and the need to strengthen community engagement to reduce stigma, discrimination, misconceptions, and misinformation ( Manda-Taylor et al, 2021 ; Mfutso-Bengo et al, 2015 ; Nyirenda et al, 2019 , 2020 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Through discussions with various stakeholders about this project specifically and MMH more generally, our study provides new insights into the acceptability and ethicality of MMH research in Malawi (and, indeed, population health research more broadly). Some of our findings reinforce and resonate with earlier studies on community perspectives around collecting biological samples in research, concerns around researchers' perceived intentions, and the need to strengthen community engagement to reduce stigma, discrimination, misconceptions, and misinformation ( Manda-Taylor et al, 2021 ; Mfutso-Bengo et al, 2015 ; Nyirenda et al, 2019 , 2020 ).…”
Section: Discussionsupporting
confidence: 80%
“…The intent is for these forms of qualitative data and consultation to iteratively inform how biomedical and public health researchers undertake GM in socially appropriate and ethically robust ways. This paper builds on formative work exploring community priorities for and concerns around MMH research in Malawi through a public (town hall) discussion event (Manda-Taylor et al, 2021) conducted in Blantyre (in the southern region). This research found that household and community consultations are essential to inform research proceedings, especially where a pregnant woman is involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, women revealed that their husbands must be consulted about the interventions they receive while attending antenatal clinic visits, particularly for interventions still under research. Male involvement in maternal health research is important, especially if it involves pregnant women, because of the practice of shared decision-making 33 . To improve the acceptability and uptake of antenatal care interventions and treatments, we continue to advocate that promoting men’s participation will encourage husbands to appreciate the importance of IV iron treatment, which can result in positive maternal and child health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We also seek to enhance our understanding of these issues in relation to traditional and religious healers, as well as health-workers including HSAs, Primary Care Health Centre and District Mental Health Team staff. We will build on our existing collaborations and work conducted in Healthy Lives, Generation Malawi [ 22 , 23 ] to do so.…”
Section: Methodsmentioning
confidence: 99%